Enhancing students’ learning outcomes using guided inquiry learning model (Research, Society and Development, 2020)
This study aims to find out the enhancement of students’ performance and motivation using guided inquiry model in High School 2 Bandar, Simalungun. The methodology used is classroom action research with quantitative and qualitative approach. This study also used pretest and posttest as data collection which done in two cycle. The result showed that guided inquiry model could increase students’ performance and learning outcomes. The enhancement can be seen from (a) their average psychomotor score in the end of first cycle for 63 to be 71 in the second cycle; (b) their affective score that increased from zero to 19% in second cycle; (c) their high response toward guided inquiry model which showed that half of the students had very positive response and the other half had positive response. The analysis of students’ cognitive study obtained through pretest and posttest had average score in first cycle for 73 and increase to 76 in second cycle. Therefore, the guided inquiry learning model can increase students’ performance and learning outcomes.